Importance of employment protection and types of employment contracts for elasticity of employment in the OECD countries - Eugeniusz Kwiatkowski; Przemysław Włodarczyk (Comparative Economic Research. Central and Eastern Europe, 2014)
This article presents the impact of the global crisis on employment in the OECD countries, and in particular is an attempt to explain why the impact is of a different scope in particular countries. Particular attention has been paid to the question of the role played by labour market institutions (such as employment protection legislation and fixed-term employment).The global economic crisis has influenced the situation in the labour markets of OECD countries, causing declines in employment and increases in unemployment. Changes in the level of employment in individual countries varied. Between 2007-2012 declines in production took place in the majority of OECD countries. Declines in real wages were also observed in those countries. On the other hand, in the period of 2005-2012 relatively small changes in labour market institutions occurred. With respect to both the stringency of employment protection legislation, as well as the share of fixed-term employment, there were no clearly visible trends in the data during the period of economic crisis.The econometric verification of theoretical hypotheses was performed using annual data from the 2005-2012 period for 26 OECD countries, and itshows that GDP and real wages were statistically significant determinants of employment size in the analyzed period. The study also confirmed the hypothesis of the existence of a non-linear (U-shaped) relationship between employment elasticity with respect to GDP and the level of stringency of employment protection legislation, as well as the share of fixed-term employment in the total number of employment contracts. The results show that the smallest declines in employment during a crisis might be expected in countries where the level of EPL is close to 2, and the share of fixed-term employment in the total number of employment contracts is close to 18%.
Keywords: 330; employment; labour market institutions; employment elasticity; employment protection; fixed-term employment